Extreme Makeover in a health center: LEAN methodology applied to clinical practice - Maria João Nuno Lopes; Sofia Monteiro (James Cook University, 2023)
Introduction: The LEAN methodology is an integration of methods and tools developed in the 90s in the industrial sector. It aims to reduce waste (things that don’t add value to the final product), add worth and work towards continuous quality improvement.Methods: LEAN tools to improve the clinical practice of a health center include:5S methodology: helps organize, clean, develop and maintain a productive work environment;'Spaghetti' diagram: displays the movement and distance that a given element has to travel throughout the entire process; andTime and motion studies: measure the various times associated with the process and the associated motion.Results: The LEAN methodology made it possible to manage space and time efficiently and optimally. There was a substantial reduction in both the time and number of trips for not only the health professionals but also for the patients.Discussion: Clinical practice should focus on the permission of continuous quality improvement. The LEAN methodology, through its different tools, generates an increase in productivity and profitability. It promotes teamwork through multidisciplinary teams and the empowerment and training of employees. The implementation of the LEAN methodology improved the practices and strengthened the team spirit based on everyone's participation, because the whole is greater than the sum of the parts.